ANALISIS KINERJA APARATUR DESA DALAM PELAYANAN PUBLIK DI KANTOR DESA NUSASARI, KECAMATAN MELAYA, KABUPATEN JEMBRANA - Ni Komang Asri Kesuma Dewi; I Gede Wirata; I Kadek Dede Junaedy (Program Studi Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Warmadewa, 2024)
This research was conducted at the Nusasari Village Office, Melaya District, Jembrana Regency. The purpose of this study was to analyze the performance of village officials in public services at the Nusasari Village Office, Melaya District, Jembrana Regency and to determine the performance constraints faced by village officials in public services at the Nusasari Village Office, Melaya District, Jembrana Regency. The research method used in this study is a qualitative descriptive method and data collection techniques through observation and interviews. The informants in this study numbered 8 people. The informants include 1 Village Head, 1 Village Secretary, 1 Head of Government Section, 1 Head of Service Section, 1 Head of Finance Section, 1 Head of Nusasari Hamlet and 2 community members. Based on the research analysis, the results of the village government in providing public services in Nusasari Village, Melaya District, Jembrana Regency as a whole can be said to be good, but in several indicators it is still not entirely in accordance with the implementation of village government performance to carry out services for the public, such as the lack of innovation in services, there are still community needs that are difficult for the village government to understand, the absence of facilities and infrastructure that are in accordance with public service indicators, such as the absence of a box for submitting suggestions, and the delivery of information related to administrative requirements is still not optimal. There are three obstacles in the implementation of village government in Nusasari Village, Melaya District, Jembrana Regency, namely the low understanding of the community regarding administrative service requirements, late disbursement of incentives and lack of discipline among the apparatus.